Future directions of psychophysical studies - Snook, S. H. (Scandinavian Journal of Work, Environment & Health, 1999)
Psychophysics is a very old branch of psychology that is concerned with the relationship between physical stimuli that occur in the ``outside world'', and the sensations they produce in the body's ``inside world''. According to modern psychophysical theory, the strength of a sensation is directly related to the intensity of its physical stimulus by means of a power function. The history and development of psychophysics is briefly reviewed, and the application of psychophysics to manual handling tasks and repetitive hand and wrist motion is described. The advantages and disadvantages of psychophysics are discussed. The following 4 directions for future research are suggested: further validation of the data, expansion into other areas of concern (eg, other body parts, jobs, and postures), broadening of the subject base by including symptomatic subjects, and greater inclusion of psychophysical measures (eg, pain, fatigue, and discomfort) in studies of musculoskeletal disorders.
Keywords: cumulative trauma; lifting; low-back pain; manual handling; repetitive motion